The Don Group : bitter end to suite dreams? (B) - Beswick, Claire; Ngendane, Lwandile; Mokoaleli-Mokoteli, Thabang (London : SAGE Publications Ltd, 2017)
By January 2011, Thabiso Tlelai, chief executive officer (CEO) of The Don Group, South Africa's largest all-suite hotel chain, knew he had to take drastic measures to save the company. With the 2008 economic recession impacting on tourist numbers to South Africa, and the 2010 FIFA World Cup increasing the number of well-funded competitors in the domestic hotel industry, The Don was struggling to register a profit and was getting deeper and deeper into debt. When Tlelai took over management of the group in 2001, he had dreamed of turning it into an international group of suite hotels. Now, he was on the verge of admitting that the dream was dead and was considering alternative strategies for the group that would still generate value for shareholders.
Originally published in Beswick, C., Ngendane, L., & Mokoaleli-Mokoteli, T. (2014). The Don Group: Bitter end to suite dreams? (B). WBS-2014-4. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Don Group; Hotels -- South Africa; Hotel management -- South Africa; Business enterprises -- Finance; Business planning -- South Africa